MULTI-SITE PRODUCT CONFIGURATION OF TELECOMMUNICATION SWITCHES - Felfernig, Alexander; Friedrich, Gerhard; Jannach, Dietmar; Russ, Christian; Zanker, Markus (International Journal of Computing, 2002)
Knowledgebased product configurators support their users in tailoring configurable products according to their specific demands and these systems have been successfully applied in many industrial sectors over the last decades. However, within today’s networked economy, the complex solutions of fered to the customers are in many cases assembled from configurable subproducts themselves. Within this paper we describe a business case where due to organisational and confidentiality reasons a singleconfigurator approach is not applicable and several configurators along the supply chain must cooperate in finding correct product configurations and in presenting them to an online customer. We present an algorithm based on Constraint Satisfaction that takes the specific characteristics of the problem domain into account and compare our approach to other work in the field of Distributed Problem Solving. The implementation framework for distributed configuration which is currently developed in the EUfunded project CAWICOMS1 is discussed in the final sections.